Advances in Manufacturing Engineering and Materials Proceedings of the International Conference on Manufacturing Engineering and Materials (ICMEM 2018), 18-22 June, 2018, Nový Smokovec, Slovakia - Hloch, Sergej; Klichová, Dagmar; Krolczyk, Grzegorz M.; Chattopadhyaya, Somnath; Ruppenthalová, Lucie (Lecture Notes in Mechanical Engineering,, 2019)
This book reports on cutting-edge research and technologies in the field of advanced manufacturing and materials, with a special emphasis on unconventional machining process, rapid prototyping and biomaterials. Based on the International Conference on Manufacturing Engineering and Materials (ICMEM 2018), held in Nový Smokovec, Slovakia on 18-22 June 2018, it covers advances in various disciplines, which are expected to increase the industry's competitiveness with regard to sustainable development and preservation of the environment and natural resources. Condition monitoring, industrial automation, and diverse fabrication processes such as welding, casting and molding, as well as tribology and bioengineering, are just a few of the topics discussed in the book's wealth of authoritative contributions.